Doppler Sonography in Infancy and Childhood - Deeg, Karl-Heinz (Springer International Publishing, 2015)
This book covers the full range of current applications of Doppler sonography in infancy and childhood, describing the variety of potential findings with the aid of a wealth of images. After an introductory chapter on the physical and technical basis of Doppler sonography, applications of cerebral Doppler sonography in infancy and of transcranial Doppler sonography in childhood are addressed, with numerous examples of imaging appearances. The major part of the book is devoted to Doppler sonography of the brain, face and neck and of the abdomen, covering normal abdominal vessels, liver, spleen, pancreas, and mesenteric and renal circulation. Imaging of the ovaries and testes is also presented, encompassing the differential diagnosis of acute scrotum and other space-occupying lesions of the testis. The book closes by considering Doppler sonography of soft tissue and vascular malformations, and the influence of congenital heart malformations on flow parameters in peripheral arteries. Doppler Sonography in Infancy and Childhood will be an invaluable reference for pediatricians, neonatologists, pediatric sonographers, and pediatric and general radiologists.
Physical and technical basics of Doppler sonography -- Cerebral Doppler sonography in infancy -- Transcranial cerebral Doppler sonography  in childhood -- Dopplersonography of the thyroid and of the soft tissue of face and neck -- Doppler sonography of normal abdominal vessels -- Doppler sonography of the liver -- Doppler sonography of the spleen -- Doppler sonography of the pancreas -- Doppler sonography of the mesenteric circulation and bowel -- Renal Doppler sonography -- Dopplersonography of the adrenal gland -- Doppler sonography of the testes -- Doppler sonography of the ovaries -- Doppler sonography of soft tissue and vascular malformations -- Influence of congenital heart malformations on flow parameters in peripheral arteries
Keywords: Radiology; Pediatrics